ANALISIS ANGKA PARTISIPASI SEKOLAH DAN TINGKAT PENDIDIKAN TERTINGGI PADA PERTUMBUHAN PRODUK DOMESTIK REGIONAL BRUTO DKI JAKARTA - Anita Ria; Heri Nurranto (Universitas Indraprasta PGRI, 2016)
This analysis is based on the perspective that, School Participation Rate and Highest Level of Education has an impact to Gross Domestic Income. DKI Jakarta to be sampled to analyze and prove the relevance of these variables. This research data is time series, where each variable research using data from 1990 through 2014. The data obtained from the Central Statistics Agency of Jakarta. The results of multiple linear regression equation, Y = 67,367,213.85 - 323,649APS + 230,162TPT. These results indicate that the figure is the School's participation in partial effect on Gross Domestic Income, with a coefficient that is 323.649, with t-test calculated at -2.212. Highest Education Level Variables proven effect on the GDP with a coefficient of 230.162, as evidenced by t-value is 9,990. Simultan Effect of variables School Participation Rateand Education Level Highest to Gross Domestic Income in the calculation result R-square of 0.908, F-value 114.62.Keywords: School Enrollment, Highest Level of Education, Gross Domestic Income